PERGESERAN BAHASA: PADA MASYARAKAT SUMATERA UTARA - T. Syarfina; Sahril Nfm (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This research is to describe language shift. The method used is qualitative method. The theory used in this research is the sociolinguistic theory of Ronald Wardaugh, Janet Holmes, R.A.Hudson, and Ralph Fasold. The location of the research was conducted in North Sumatera Province. In terms of seeing language shifts, researchers take data from multiple sources. The results of the analysis of the occurrence of language shift is due to the attitude of language, code transfer, code mix, and the tendency to use foreign terms.